Perancangan Sistem Informasi Penjualan, Produksi dan Persediaan pada PT Triwarna Eka Multimedia - Surja, Stephanie; Sanjaya, Lius Steven (Bina Nusantara University, 2014)
The idea to design an information system in PT Triwarna Eka Multimedia arises because of the current information system is still very traditional and it has an enormous dependency to physical data. Designing of an information system in PT Triwarna Eka Multimedia is aimed to identify the organization needs in managing their business process operational related to current data of sales, production and inventory. The result from those processes is aimed to build an integrated system that can meet all of the organization?s needs in running their daily business process and facing the rivalry from the competitors. The method used in this paper is a survey, literature review, and analysis of current business processes in the company These needs will be documented by using unified modeling language. This information system makes all the current operational business activities easier with the more enhanced automation than the previous information system. This system will also minimize the data lost and human error, which is usually cause by the manual process and storage data of physical data.